The role of organophosphate exposure in the aetiology of depression and suicidality amoungst farm workers on wine and table grape farms in the Worcester area of the Western Cape Province, South Africa - Major, Viveca Joy (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.